m-kreuzer/MOM5: Version as used in Kreuzer et al., Geoscientific Model Development publication (doi 10.5194/gmd-14-3697-2021) - Tim Leslie; Marshall Ward; Nic Hannah; Nicholas Hoover; Aidan Heerdegen; Stephen Griffies; Andrew Kiss; russfiedler; Ryan Holmes; Hailin Yan; Riccardo Farneti; Paul Leopardi; et al. (Zenodo, 2020)
This is a MOM5 code release as used in the Geoscientifc Model Development publication "Coupling framework (1.0) for the PISM (1.1.4) ice sheet model and the MOM5 (5.1.0) ocean model via the PICO ice shelf cavity model in an Antarctic domain" by Moritz Kreuzer, Ronja Reese, Willem Huiskamp, Stefan Petri, Torsten Albrecht, Georg Feulner and Ricarda Winkelmann.